Identification of factors affecting adoption of mobile payments among hawkers using UTAUT (2021) - Lukmantara, Jessica A (Nanyang Technological University, 2022)
Mobile payments have become the new norm in Singapore’s payment landscape today. This study attempts to identify the factors that are affecting hawkers’ intention to adopt SGQR or QR payments, based on a modified Unified Theory of Acceptance and Use of Technology (UTAUT) model. External factors like incentive, perceived risk and perceived cost were added to the revised model. The effects of age, education level and average price range as moderating variables were also explored. A total of 100 hawkers were surveyed. Utilizing Partial Least Square Structural Equation Model (PLS-SEM), performance expectancy, effort expectancy and incentive were revealed to have positive and significant effects on hawkers’ intention to adopt mobile payments. The results can serve as a guide for policymakers who wish to improve mobile payments adoption rate among hawkers.